Development of a modified trauma and injury severity score to predict disability in acute trauma patients - Ki Jeong Hong; Kyoung Jun Song; Sang Do Shin; Young Sun Ro; Jeong Ho Park; Seung Chul Lee; Chu Hyun Kim (Clinical and Experimental Emergency Medicine, 2020)
Objective The Trauma and Injury Severity Score (TRISS) has been used to predict trauma patient mortality and to assess the quality of trauma care systems. The goal of this investigation was to develop a modified trauma-related injury severity score (termed the TRISS-D) for predicting disability in acute trauma patients. Methods We used data collected by emergency medical services and entered into the Korea Centers for Disease Control and Prevention severe trauma database. The TRISS-D was based on age category (0–14, 15–54, ≥55 years), the Revised Trauma Score, and the Injury Severity Score. The outcome measures were severe disability and worsening disability. Worsening disability was defined as a lower Glasgow Outcome Scale score at hospital discharge than before the traumatic incident. Two types of cases were examined: those with penetrating or blunt injuries (group 1) and those with severe head injuries (group 2). We assessed the discriminatory power of the TRISS-D by calculating the area under a receiver operating characteristic curve (AUROC). Results The database comprised 14,791 patients; overall, 3,757 (25%) had severe disability and 6,018 (41%) had worsening disability. For severe disability, the AUROC (95% confidence interval) for the TRISS-D was 0.948 (0.944–0.952) in group 1 and 0.950 (0.946–0.954) in group 2. The corresponding values for worsening disability were 0.810 (0.803–0.817) and 0.816 (0.809–0.823), respectively. Conclusion The TRISS-D showed excellent discriminatory power for severe disability and very good discriminatory power for worsening disability.